Karakteristik Metodologis dan Tafsir Teologis Al-Asfahani dalam Kitab Tafsir Ar-Raqib Al-Asfahani - Nurul Huda (Analisa: Journal of Social Science and Religion, 2010)
This is a library research on kitab Tafsir ar-Ragib al-Asfahani. This studyaims to draw characteristic of methodology Tafsir ar-Ragib al-Asfahani andtheological exegesis. Method of this research is factual history and eclectic(principle of skepticism). This method shows many characteristics of methodologyOf Tafsir ar-Ragib al-Asfahani and al-Asfahani’s theological exegesis, and inclination of al-Asfahani toward theology of ahlusunah. However, This preference is not the main pattern of his exegesis. That Characteristic of methodology divers based of time, method, form and types. Keywords: Methology, Exegesis, Ar-Ragib al-